Association of race, ethnicity, and socioeconomic characteristics as predictors of cachexia risk and survival in stage IV non–small cell lung cancer (NSCLC). Issue 28 (1st October 2022) - Olaechea, Santiago; Liu, Alison; Sarver, Brandon; Alvarez, Christian; Gilmore, L Anne; Infante, Rodney E; Iyengar, Puneeth
Abstract : 151 Background: Cachexia, seen in more than a third of patients with non-small cell lung cancer (NSCLC), directly leads to functional and survival detriments. As screening and interventions for cachexia and NSCLC improve, deficits of healthcare access and quality among patients disadvantaged by race and socioeconomic factors must be addressed. Methods: Through retrospective and prospective data collection, we established a cohort of 957 patients diagnosed with stage IV NSCLC between 2014-2020 in Dallas, Texas. Presence of cachexia at diagnosis was determined using consensus criteria for substantial (5% for BMI≥20 and 2% for BMI < 20) unintentional weight loss in the 6 months leading to diagnosis. Analyses including multivariate logistic regression and log-rank testing evaluated for significant associations of variables with cachexia incidence and survival. Results: Black race and Hispanic ethnicity independently associated with more than a 70% increased risk of cachexia at NSCLC diagnosis (Table; P < 0.05). Inclusion of private insurance status as a covariate diminished this finding for Hispanic patients only. Black patients presented at younger ages than White patients (Kruskal-Wallis P =0.0012; T-test P = 0.0002), with an average difference of 3 years. Cachexia at diagnosis was a major predictor of survival, highlighting the importance of addressing differential cachexia risk across race/ethnicity. Conclusions: The elevated cachexia risk observed for Black patients independent of insurance status reveals broader causative factors of disparity. A lack of private insurance may be a primary contributor in Hispanic cachexia prevalence. Targeting these differences could mitigate survival detriments linked to cachexia in minority groups. Supported contributors in broader NSCLC outcome inequities include poor representation in trials substantiating USPSTF guidelines as well as preventable barriers to primary and preventative care. Our interpretation of NSCLC outcome disparity in the context of cachexia demonstrates further consequences of these deficits. Moreover, our findings suggest novel targets for health policy by highlighting the prevalence of undiagnosed unintentional weight loss in minority populations with late-stage NSCLC.Multivariate analysis of cachexia incidence at cancer diagnosis. Parameter Odds ratio (95% CI) P-value Age at diagnosis 1.00 (.99-1.02) .5675 Female Sex .70 (.51-.96) .0287 Race Non-Hispanic White - .0089 Black 1.75 (1.21-2.54) .0033 Asian .91 (.45-1.81) .7816 Hispanic 1.72 (1.01-2.93) .0477 Charlson comorbidity score 1.00 (.95-1.06) .8953 Pretreatment BMI .98 (.95-1.00) .1166 Alcohol use .99 (.72-1.37) .9588 Tobacco use 1.63 (1.06-2.50) .0257 Histology Adenocarcinoma - .2591 Squamous 1.40 (.93-2.12) .1084 Large Cell 1.28 (.43-3.82) .6591 Mixed 1.46 (.87-2.44) .1539